FMRI evidence for a reduction in affective processing of thermal pain in responders of transcutaneous vagal nerve stimulation (TVNS). Issue 3 (March 2016) - Laqua, R.; Lotze, M.; Leutzow, B.; Usichenko, T.
Abstract : Background: Although the transcutaneous vagal nerve stimulation (TVNS) is increasingly used in treatment of chronic pain, the underlying mechanism is unclear. The goal of this study was to analyse the cerebral effects of TVNS under experimental pain in fMRI. Methods: Twenty healthy volunteers took part in two separate fMRI sessions (3 Tesla) with experimental pain, which was applied to the right forearm with MEDOC Sensory Analyser. During TVNS session the electrical stimulation was applied bilaterally to auricular concha with rectangle impulses (8 Hz frequency; 200 μs wave length); the intensity was maximal but not painful. During placebo session the stimulation device was switched off. The order of the sessions was randomised. Individual sensory thresholds were registered before and after each fMRI session. fMRI data was afterwards processed with standard settings in SPM8 and differences in BOLD effects between verum and placebo session were calculated. We used region of interest (ROI) based analysis on ROIs, which were previously identified in association with thermal pain. Results: Cerebral pain processing areas were activated bilaterally under thermal stimulation. The group analysis did not show the differences in sensory parameters but revealed stronger activation of right amygdala under TVNS. The group of responders (subjects with increased pain threshold after TVNS, n = 8), showed a reduction in BOLD signal in the right nucleus caudate, the middle frontal cortex and left hypothalamus under TVNS in comparison to placebo. Conclusion: Thermal stimulation elicited bilateral fMRI activation in pain processing regions of the brain in healthy volunteers. Responders to TVNS showed decreased activation in cerebral areas associated with affective processing of pain.